The use of renal replacement therapy in critically ill pediatric small bowel transplantation candidates and recipients: Experience from one center. (26th March 2015) - Pineda, Carol; Grogan, Tristan; Lin, James A.; Zaritsky, Joshua J.; Venick, Robert; Farmer, Douglas G.; Kelly, Robert B.
Abstract Outcomes for pediatric SBT patients requiring perioperative RRT in the PICU remain unknown. The objectives were to document our center's experience with PICU SBT patients receiving perioperative RRT and to identify variables predictive of survival to discharge. A retrospective chart review of patients (ages, 0–18 yr) between January 1, 2000 and December 31, 2011 that received RRT within a SBT perioperative period and were transplanted at our university‐affiliated, tertiary care children's hospital was performed. Six SBT patients received perioperative RRT (ages, 5–12 yr). Three patients (50%) survived to hospital discharge. Among survivors, RRT was required for a total of 1–112 days (mean, 49.7 days). All three survivors survived to hospital discharge without renal transplantation and free of RRT. There was a trend toward increased survival among older patients receiving RRT (p = 0.05). Survivors had a higher I‐125 GFR prior to PICU admission (p = 0.045). A higher I‐125 GFR prior to PICU admission among survivors may support this test's utility during SBT evaluation. In our experience, a high survival rate and freedom from RRT at the time of discharge support RRT use in the SBT population.